Equilibrium and non-equilibrium free carrier dynamics in 2D Ti3C2Tx MXenes: THz spectroscopy study. (27th June 2018) - Li, Guangjiang; Kushnir, Kateryna; Dong, Yongchang; Chertopalov, Sergii; Rao, Apparao M; Mochalin, Vadym N; Podila, Ramakrishna; Titova, Lyubov V
Abstract: MXenes is an emerging class of 2D transition metal carbides, nitrides and carbonitrides which exhibit large conductivity, ultrahigh volumetric capacitance, high threshold for light-induced damage and nonlinear optical transmittance, making them attractive candidates for a variety of optoelectronic and electrochemical applications. Here, we report on equilibrium and non-equilibrium free carrier dynamics of Ti3 C2 T x gleaned from THz spectroscopic studies for the first time. Ti3 C2 T x showed high (~2  ×  10 21 cm −3 ) intrinsic charge carrier density and relatively high (~34 cm 2 V −1 s −1 ) mobility of carriers with an exceptionally large, ~46 000 cm −1 absorption in the THz range, which suggests that Ti3 C2 T x is well suited for THz detection. We also demonstrate that Ti3 C2 T x conductivity and THz transmission can be manipulated by photoexcitation, as absorption of near-infrared, 800 nm pulses is found to cause transient suppression of the conductivity that recovers over hundreds of picoseconds. The possibility of control over THz transmission and conductivity by photoexcitation suggests the promise for application of Ti3 C2 T x Mxenes in THz modulation devices and variable electromagnetic shielding.